Standardization of distance and angulation of light curing unit tip using distometer - Radzi, Z.; Abu Kasim, Noor Hayaty; Yahya, N.A.; Abu Osman, Noor Azuan; Kassim, N.L. (2007)
The purpose of this study was to investigate the light intensity of selected light curing unit with varying distance and angulation of the light curing tip and lightmeter.